Hannes Kerber and Svetozar Y. Minkov (a cura di), Leo Strauss on Plato’s Euthyphro. The 1948 Notebook, with Lectures and Critical Writings, The Pennsylvania State University Press, University Park (Penn) 2023, pp. 231 - Menon, Marco (Filosofia Morale/Moral Philosophy, 2024)